Introduction to Finite Elemennts In Engineering - Chandrupatla (Tripathi R); Belegundu (Ashok D) (2006)
Finite Element Analysis
32457a.jpg;32457b.jpg;32457c.jpg;32457d.jpg;32457e.jpg;32457f.jpg;32457g.jpg
22.5
Keywords: Finite Element Analysis